Business Management Development Model For “Cireng Ceu Iin” Enterprises In Padasuka Village, Baros District, Serang Regency - Khaeruman; M. Ilmi Syiraf; Defi Mugfiroh; Yeny Safriyana; Fariha Maulani; Difa Ramadani Nurhidayati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Marketing is a business function that identifies current unmet wants and needs and manages their size, determines which target markets the organization can best serve, and determines the appropriate range of products, services and programs to serve those markets. So marketing acts as a liaison between the needs of the community and the pattern of industrial responses.This community service activity is carried out at the home of the business actor who has the address. The method used in the implementation of community service activities is business assistance.The purpose of this method is the participatory-lecture method,discussion-information and continued with direct training on making business management development models for business actors